Health aspects of aerobic interval training in the rehabilitation of the patients with cardiovascular diseases - Tamara Ilić; Doroteja Rančić; Stefan Stojanović; Ismail Ilbak (ANNALES ZRS, Scientific Publishing House of ZRS Koper, 2023)
Purpose: The aim of this study was to review the literature analyzing the effects of aerobic interval training in the rehabilitation of cardiovascular patients. Methods: Research data was collected considering the inclusion and exclusion criteria of the research studies published in English. In order for the study to be included in the analysis, it had to meet the following criteria: year of publication (2004-2022), respondents were people with cardiovascular disease, and the studies included in this review must contain data on disease, training programme and outcomes. Papers without full texts available and systematic review studies were excluded. The first search identified 71 articles. In the initial assessment carried out in accordance with the inclusion and exclusion criteria, 15 articles were found suitable and were included in the study, while 20 studies were excluded for being duplicates, 28 studies excluded for not having the full text available and eight for non-compliance. Results: The reviewed materials indicate that aerobic interval training has an impact on VO2 max, functional abilities, Vo2 peak and functional capacity in the rehabilitation of cardiovascular diseases, especially in the elderly. The duration of the programme in most studies has a similar time range from 10 to 16 weeks. The programmes that showed the best effects are related to aerobic interval training, from 2 to 3 times per week with moderate (50-60% of VO2 max) or high intensity (80-90% of VO2 max). Conclusion: Studies indicate that properly dosed physical activity contributes to a better lifestyle for people with cardiovascular diseases. All 15 studies showed positive effects of aerobic interval training in cardiovascular disease rehabilitation.